Impact of emerging strains of canine parvovirus - Moore, Jennafer (Kansas State University, 2021)
Canine parvovirus 2 (CPV-2) is an extremely contagious virus that causes high morbidity and mortality in canines, especially pediatrics. The virus was first discovered in 1978, while it was in the midst of a global pandemic. Since this time, it has remained at the forefront of veterinary medicine. Canine parvovirus 2 causes acute hemorrhagic enteritis and myocarditis, both of which are very difficult for canines to recover from, making it one of the leading causes of death. Viral shedding occurs through the feces of infected animals that occurs during the incubation period, and it spreads through contact with individuals and fomites. Canine parvovirus 2 is a robust virus, having the ability to resist many disinfectants and survive in contaminated soil for up to 5 months or longer. Additionally, there are ongoing issues that include the failure of available vaccines in providing adequate protective immunity and the lack of some in-clinic diagnostic assays to positively identify the virus. New strains of the virus, such as CPV-2c, have evolved over the last 30 years, and they have also spread all over the world. All of these factors have led to the inability to contain the virus and its disease manifestation. The purpose of this report is to understand how strains of canine parvovirus have emerged over the years as well as to describe the impact of new strains on canine health.
Keywords: Canine parvovirus 2